Rorippa sylvestris (L.) Bess., a Newly Naturalized Mustard Species in Taiwan - Tsung-Hsin Hsieh (Taiwania, 2005)
Rorippa sylvestris (L.) Bess., a species of the Brassicacae widespread in SW Asia and Europe, was recently found naturalized at ca. 1500 m altitude in central Taiwan. Morphologically, R. sylvestris resembles R. palustris, both having deeply pinnatifid leaves, but can be distinguished from R. palustris by similar size pinnules, slender pedicels in fruiting stage (8-12 mm) and linear fruits. SEM micrographs of pollen grains, chromosome number, descriptions, line drawing and taxonomic notes are provided.